The Effect of the Covid-19 Pandemic, Liquidity, Leverage, and Intellectual Capital on Company Value - Dewi, Ni Putu Sandra Susila; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 35 No 6 (2025), 2025)
This study aims to explore the effects of the COVID-19 pandemic, leverage, liquidity, and intellectual capital on firm value. It analyzes a sample of 79 non-cyclical consumer companies listed on the Indonesian Stock Exchange (IDX) during the specified observation period, culminating in 311 data points. A purposive sampling technique was employed, which selectively included companies based on set criteria, thus not representing the entire population equally. Data were analyzed using multiple linear regression, revealing that while the COVID-19 pandemic did not affect firm value, leverage had a negative impact. Conversely, liquidity and intellectual capital were found to positively influence firm value. The findings provide valuable insights for stakeholders regarding the determinants of firm value under the influence of varying economic conditions.  Keywords: Company Value; Covid-19 Pandemic; Liquidity; Leverage; Intellectual Capital